Analysis of the Relationship between Learning Environment and Student Engagement 个体背景和学习环境因素对来华本科留学生学习投入的影响: A Case Study of International Undergraduate Students in China - Lu, Genshu; Li, Lijie; Tian, Mei (Journal of International Students, 2020)
Drawing on the data generated by a survey involving 1,428 international undergraduate students in China, this article analyzed the relationship between the participants’ perceived learning environment and their self-reported engagement in academic activities. The findings revealed the participants’ uneven participation in academic activities. Based on their self-reported levels of student engagement, the participants were categorized into three types: i.e. active engagement (23.2%), lack of engagement (45.8%) and inadequate engagement (31.0%). In line with the previous research findings, this research confirmed a significant relationship between international students’ perceived learning environment and their engagement in academic studies. Suggestions were given for the enhancement of international student education in China. 本研究应用对1428名来华本科留学生的调查数据，探讨了来华留学生的学习投入状态，以及个体因素和学习环境因素对其学习投入的影响。研究发现，就总体而言，来华本科留学生感知的学习环境处于良好状态，他们的学习投入程度则处于一般偏低水平；根据来华本科留学生学习投入情况，可将其学习投入类型分为高投入型、低投入型和欠投入型三类，分别占比23.2%，45.8%，31.0%；个体因素和学习环境因素对来华本科留学生的学习投入程度具有一定的显著影响。为提高来华留学生的学习投入程度，一方面要从来华留学生自身出发，提高学习自觉性，增强学习投入水平；另一方面，要根据来华本科留学生的个体背景采取胡针对性的策略，同时通过营造良好的学习环境来提升来华本科留学生的学习投入水平，帮助其获得更好的在华留学经历。